Konsepsi Qur’ani tentang Fakir dan Miskin (QS. At-Taubah: 60; Al-Baqarah: 273) dan Relevansinya bagi Mekanisme Penetapan Sasaran Program Keluarga Harapan (PKH) - Sri Yuliyawati (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the relevance of the concepts of faqir and miskin (the poor and the needy) from the perspective of the Qur’an and its exegesis (tafsir) to the targeting mechanism of Indonesia's Program Keluarga Harapan (PKH) or Family Hope Program. Employing a qualitative approach with library research and document analysis methods, this research conducts an in-depth examination of the interpretations of QS. At-Taubah verse 60 and QS. Al-Baqarah verse 273 concerning faqir and miskin, as found in the classical commentaries (tafsir) of Al-Misbah by Quraish Shihab and Al-Maraghi by Ahmad Mustafa al-Maraghi. The findings reveal a significant gap between the Islamic conceptualization of poverty and the implementation of PKH’s targeting criteria. The Islamic concept emphasizes a holistic approach encompassing both material and spiritual dimensions, while PKH tends to focus predominantly on material-economic aspects. Notably, PKH’s current mechanism overlooks the core Islamic value of ta’affuf (self-respect and refraining from begging) as articulated in QS. Al-Baqarah: 273. Consequently, the study recommends integrating these spiritual values into the PKH targeting system. Key recommendations include operationalizing the principle of ta’affuf and implementing a graded assistance system based on levels of vulnerability, as implied by the differentiation between faqir and miskin in QS. At-Taubah: 60.